АБАЙ ИЛИМИНДЕГИ ТУТАСЛЫҚ: АҚЫЛЛЫ ҚАРА ҚЫЛДЫ ҚЫРЫҚҚА БӨЛМЕК - Салқынбай, А.Б. (ILIM hám JÁMIYET, 2025)
The article examines the philosophical views of the famous poet Abai as carriers of national culture and the worldview of the Kazakh people.